La editorial CALPE y el Catálogo general de 1923 - Sánchez Vigil, Juan Miguel (Documentación de las Ciencias de la Información, 2006)
This article aims at analysing the history of archives and their documentary practice through indirect sources. These sources may not have as their main objective an analysis of institutions and their documents, but offer significant accounts of the social perception of archives and their professional use. Our research, therefore, has three main aims: determining the theoretical foundations of the culture history of archives, establishing an analysis of social perception as a valid tool for historical research on archives and, finally, making this methodology explicit through an assessment of a wide range of indirect documentary sources.